A emoção na criança de 3 a 4 anos: laços de alteridade e mediações entre escola e família na educação infantil em meio à pandemia da covid-19. - Nobrega, Isabelle (Universidade Federal de São Carlos, 2021)
This research aims to analyze a trajectory of the meanings of emotions historically constituted by a group of children aged 3 to 4 years in social isolation caused by the Covid-19 Pandemic. The children belong to a room at the Child Care Unit (UAC) at the Federal University of São Carlos - UFSCar, campus São Carlos-SP. Resulting from the Covid-19 pandemic, the project was developed in a virtual environment, using applications such as Whatsapp and Google Drive to dialogue with the children's families, as well as sending suggestions for weekly activities addressing the theme of emotions. Based on the theoretical construct of the philosopher of language M. Bakhtin and authors who compose a cultural-historical theory such as Vygotsky, Luria, Leontiev, among others who understand language as a constitutive activity of consciousness and emotions, reports and narratives were collected. of family members about their children at this moment of social isolation in order to analyze whether the proposed activities helped in understanding the meaning of different emotions for children. This research will contribute to the areas of Linguistics, Psychology and Education, as it seeks to highlight the importance of naming emotions during childhood for the child's emotional and intellectual development. Frontal data in the light of the theoretical framework allow public policies to incorporate the theme "Emotion and Feelings" in the Early Childhood Education curriculum, as well as seeking to help teachers to work on this theme in the classroom, welcoming families and their children, especially when returning to face-to face activities during and after the Covid-19 pandemic.
The emotion in children aged 3 to 4: bonds of otherness and mediations between school and family in early childhood education during the covid-19 pandemic.
Keywords: Linguagem; Emoção; Literatura infantil; Educação infantil; Language; Emotion; Children's literature; Child education; CIENCIAS HUMANAS